SPECTROSCOPIC INVESTIGATIONS OF GALACTIC CLUSTERS WITH ASSOCIATED CEPHEID VARIABLES. III. COLLINDER 394 AND BB SGR - Usenko, I. A.; Kniazev, A. Yu.; Katkov, I. Yu.; Kovtyukh, V. V.; Mishenina, T. V.; Miroshnichenko, A. S.; Turner, D. G. (Одеські астрономічні публікації, 2019)
We present the results of a spectro- scopic and photometric investigation of 20 objects from the open cluster Collinder 394, which contains the Cepheid BB Sgr. Besides the Cepheid, we studied tree K-giants, four B-giants, and twelve B-A-F main sequence stars. Radial velocities (RV), vsini, T eff , logg, were determined using spectroscopic model fitting and atmosphere models. We have derived the color-excesses, reddenings, and intrinsic colors for these stars using their T eff and logg from compar- ison to the atmosphere models, especially for hot stars. Proper motions, RV and GAIA DR2 2018 parallax/distance values for these stars allowed us to determine their membership in the cluster and absolute magnitudes. We found that seven stars do not belong to the cluster. The parallaxes and reddenings of 13 confidently cluster members led to the distances in a range of 630–800 pc, although the majority of them (8 objects) are located at a mean distance of 657.7±66.7 pc, and 5 objects with the Cepheid could probably belong to the cluster’s corona. All the members have [Fe/H] near 0.1 dex. The main sequence B-star No. 76 (HD 174307) has a low rotational velocity projection, and this fact allows us to determine its chemical composition to compare with that of the Cepheid BB Sgr. Its CNO and Na abundances are close to the solar one, while the Cepheid show a deficit of carbon, an overabundance of nitrogen, nearly solar oxygen, and an overabundance of sodium. Three foreground K-giants have different C abundances (from a deficit to the solar), and Na (from the solar to an overabundance) as well as a solar-like O content. The foreground F7-8 V star No. 75 (CPD −20 ◦ 7218) was revealed to be a Li-rich star, while the A7 V star No. 69 (BD −20 ◦ 5290) has an anomalous deficit of CNO with overabundances of some α, r- and s-process elements.